Diagnostic Overlap between Arrhythmogenic Right Ventricular Cardiomyopathy and Myocarditis - Dalia, Tarun; Sami, Farhad; Dalia, Arushi; Gautam, Archana; Dehkordi, Seyed Hamed Hosseini; Khashab, Mohamed El (Cardiology and Cardiovascular Medicine, 2021)
Background: Arrhythmogenic Right Ventricular Cardiomyopathy/Dysplasia (ARVC/D) is an inherited cardiomyopathy. Case: 20 years old male had out of hospital cardiac arrest while playing basketball. Bystander CPR was started immediately, and ROSC was achieved after 2 shocks for Vfib. He was intubated and urgently taken to the local cardiac catherization lab. LHC showed normal coronary anatomy. Echo showed biventricular failure with LVEF of 5-10%. He was transferred to our hospital for advanced heart failure therapies. EKG showed normal sinus rhythm with T wave inversions in V1-V3 lead, normal QTc. Emergent RHC with endomyocardial biopsy was performed. Decision was made to proceed with VA-ECMO placement for cardiogenic shock. The biopsy showed inflammatory infiltrate and focal associated myocyte damage. He started showing signs of recovery on day 2 without needing immunosuppressive medications. He was diagnosed with myocarditis and discharged on day 7 with full LVEF recovery. One month later, he is asymptomatic. His echo shows dyskinetic and dilated RV with normal LV. Genetic testing showed PKP2 mutation. Hence, the diagnosis was modified to ARVC/D. Conclusion: ARVD poses a diagnostic challenge, high index of clinical suspicion is required. Myocarditis can mimic ARVD. VA-ECMO can be utilized as bridge to recovery in these patients.